Effects of in vitro plant ages on the subsequent growth of Plumbago indica l. after ex vitro transplantation - Khoa, Tran Tu; Duy, Pham Minh; Huong, Tran Thi; Quynh, Nguyen Thi (Academia Journal of Biology, 2021)
The Indian leadwort (Plumbago indica L.) of the family Plumbaginaceae is a plant with high pharmaceutical value, as it contains plumbagin, a naphthoquinone with antibacterial, antifungal and anticancer properties. Among the propagation methods for the Indian leadwort, in vitro propagation is considered an effective method in producing disease-free transplants in a short period of time with high propagation rate. When plants grown in vitro are transferred to ex vitro condition, the environmental factors in the nursery house such as light, temperature, humidity and microorganism in the soil will affect their growth. Characteristics of transplants themselves is also critical for the subsequent growth. It is, thus, essential to establish the standards to evaluate and qualify in vitro plants for transplanting to ex vitro condition. Among these standards, the culture age of in vitro plants affects the maturations of their root, stem and leaves, which can in turn influence the acclimating ability and growth of in vitro plants after transplantation. The purpose of this study is to investigate the effects of the culture age of in vitro Indian leadwort plants on their performance during ex vitro stage. For this purpose, three different culture ages of uniform in vitro plants, 35, 42 and 49 day-old, were studied. After 28 days of cultivation in the nursery house under the light intensity of 70 ± 10 µmol m-2 s-1, temperature of 35 ± 4 oC and relative humidity (RH) of 60 ± 10%, all three treatments achieved 100% survival rate. Increased fresh and dry weights and percentage of dry matter after cultivation in ex vitro condition were not statistically different between 42 day-old and 49 day-old in vitro plants, but were significantly different between these plants and 35 day-old in vitro plants. The development of shoot and root in ex vitro stage of 42 day-old and 49 day-old in vitro plants was more balanced, as shown by the higher ratio of shoot/root dry weight, than 35 day-old in vitro plants. The results of this study showed that for this Plumbago species, bigger in vitro plants led to better growth during ex vitro stage. These results also indicated that it was possible to transfer in vitro Plumbago plants to ex vitro condition after 5 weeks of in vitro culture stage.